Percepção e memória na filosofia de Henri Bergson - Pellegrino, Rafael (Universidade Federal de São Carlos, 2015)
This text aims to present a particular reading of Matter and Memory, one of the leading books of Henri Bergson's work. It follows the route of Bergson's answer to the problem of duality of soul and body, spirit and matter, seeking to define the key points of a bergsonian theory of the soul. Therefore, the reading that follows here is limited to give special attention to the psychological issues of the book, opening up gradually, and as necessary, to metaphysics involved in these issues. Three main points of Matter and Memory will be analyzed to reveal the Bergsonian psychology of levels of consciousness and the dynamic process of the soul: the theory of pure perception, the circuit of attention and the figure of cône mobile. As will be seen, these points represent a gradual movement searching to define the true nature of the body's relationship with the spirit, and reflect a redefinition of the roles of the body and also the memory. Defined, finally, the role of effort as the inherent process in the body's relationship with the psychic, this work is concluded at the exact point where the soul and the duration appear as inextricably linked, taking the same nature. At this point the text closes, exactly where the doors are opened to metaphysics. At this point this text closes, just to open the doors for metaphysics.
Keywords: Subjetividade; Consciência; Corpo; Duração (Filosofia); Memória; Percepção (Filosofia); Consciousness; Body; Duration; Memory; Perception; CIENCIAS HUMANAS::FILOSOFIA